2019
DOI: 10.1002/mop.32218
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of rectifier stage number and load resistance in an RF energy harvesting circuit

Abstract: In this study, a single‐stage and three‐stage Dickson rectifier circuits that would be able to perform RF energy harvesting were proposed. Operating frequency was selected as 1 GHz. The highest efficiency value was obtained at 7 dBm input power. The load resistance values for the input power were parametrically analyzed and the power conversion efficiency and output voltage were calculated. In the cases where the best performance was obtained, while a maximum power conversion efficiency of 70.5% was obtained i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…The efficiency of this work is 33% for −7 dBm input power. The authors have used HSMS-285C diodes in [46] to manufacture and compare a 1-stage Dickson rectifier and a 3-stage Dickson rectifier. The circuits tune in 1 GHz and for −7 dBm input power.…”
Section: Diodesmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficiency of this work is 33% for −7 dBm input power. The authors have used HSMS-285C diodes in [46] to manufacture and compare a 1-stage Dickson rectifier and a 3-stage Dickson rectifier. The circuits tune in 1 GHz and for −7 dBm input power.…”
Section: Diodesmentioning
confidence: 99%
“…[41] HSMS2820 Dual-Stage Voltage Doubler [42] SMS7630-079 3 Rectifiers in Series [43] SMS7630 Voltage Doubler [45] SMS7630 Single Diode Rectifier [46] HSMS-285C 1-Stage Dickson Rectifier [47] HSMS 286C Rectifier…”
Section: Reference Diode Circuitmentioning
confidence: 99%
“…Various rectifier designs, such as single frequency [4][5][6][7][8][9], dual-band [10][11][12][13][14][15][16][17][18], tri-band [19][20][21][22][23][24][25], quad-band [26][27][28], and broadband [29], are used to create an efficient rectifier.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Xiao et al [5] and Kasar et al [6] proposed high efficiency (>70%) single frequency rectifiers, but they operate at higher input power (>7 dBm).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In order to provide an adequate load for each stage of the rectifier circuit, a load block composed of two Schottky diodes HSMS2820 (DL1 and DL2) is proposed as shown in Figure 5. Theoretical 8 and experimental 10 studies have demonstrated that each Schottky diode‐based rectifier circuit has its own optimal value of the load resistance where the PCE is optimal. The optimal load values for the first and second stages of the conversion block are R Load1 = R 1 + R 2 and R Load2 = R 1 , respectively, where R 1 = 1 kΩ and R 2 = 0.3 kΩ.…”
Section: Rectifier Design and Measurementmentioning
confidence: 99%